ANALISIS FAKTOR DAN PERILAKU YANG MEMPENGARUHI PERSEPSI WAJIB PAJAK TENTANG PENGGELAPAN PAJAK - Kelvin, Kelvin; Rosyadi, Mohammad Eddy (E-Jurnal Akuntansi TSM, 2024)
Major funding for the state revenue in Indonesia comes from taxes. With tax revenues, the government finances all state expenditures, both routine and developmental, aiming to enhance the prosperity and welfare of the people. However, many government efforts to increase tax revenue do not meet expectations due to the low awareness of taxpayers in fulfilling their tax obligations. This research aims to examine the factors influencing taxpayers' perceptions of tax evasion. It is a primary quantitative study using a questionnaire distributed to taxpayers registered in KPP Pratama Tambora and KPP Pratama Tamansari. The research sample consists of 122 respondents, analyzed using multiple analysis techniques.The results of this study indicate that love of money, discrimination in taxation, understanding of taxation, and subjective norms influence taxpayers' perceptions of tax evasion. However, other independent variables, namely the tax system, tax justice, and religiosity, do not affect taxpayers' perceptions of tax evasion.